Behavior of Social Development By Performers of Narcotics Abuse as A Source of Social Studies Learning - Tartila, Tengku Syarifah Soraya (Universitas Pendidikan Indonesia (UPI), 2022)
This research is motivated by several facts about the morality of social phenomena occurred in Indramayu Regency, namely the increasing abuse of narcotics among the people of Indramayu, especially students. One way to anticipate these problems is through efforts to prevent narcotics abuse by disseminating the impacts of social studies learning. This research uses case study method. Data collection techniques were carried out by means of interviews, documentation studies and direct observation to the main data sources and supporting data sources, which were integrated into the Social Sciences curriculum for Junior High School, namely the Social Deviance Competency Standard with cases of narcotics abuse to determine the extent to which the social studies learning process could improve students' understanding of abuse. narcotics, the social impact it causes and how to avoid it. The results of this study describe (1) the causes of narcotics abuse that become social deviant behavior in Indramayu Regency, namely the environmental conditions around the users such as geographic, demographic, and socio-cultural factors, as well as external and internal reasons from within the narcotics users, namely family, friends, curiosity and frustration (2) efforts made by users to get out of the bondage of narcotics types of marijuana and methamphetamine such as wishes to recover and rehabilitation efforts organized by the victim's family as well as related agencies which are very helpful for users (3) Integration narcotics abuse material into the Competency Standards of social deviation in junior high school which provides an increase in understanding before and after learning significantly better with the results of high category analysis, cognitively with increasing student knowledge, morally/values build positive attitudes and characters in themselves. resulting from the learning process, as well as behavior change as a manifestation of both.